Tuberous plants with active compounds against helminths in livestock: A systematic review : The role of plants with medicinal value to livestock production and health - Mpofu, Mellisa; Mugumbate, Grace; Gomo, Calvin; Mashingaidze, Arnold Bray; Chikwambi, Zedius; Murungweni, Chrispen (Ethnobotany Research and Applications, 2022)
Background: The rise in drug-resistant to helminths has posed a challenge on conventional techniques of controlling parasitic illnesses in livestock. Using less conventional approaches such as plant extracts on the other hand, is encouraged. This research explored tuberous plants used in developing anthelmintics and identified active compounds associated with the plants. Methods: From October 2020 to February 2021, a comprehensive literature search was conducted using search engines such as Google Scholar, NISCAIR Online Periodicals Repository, NCBI, Taylor and Francis Online, Wiley Online Libraries, Science Direct, ResearchGate, and Springer Link. This evaluation included only ethnobotanical papers that showed tuberous plants with anthelmintic properties. Results: Forty-eight ethnobotanical investigations recorded plants with tuber portions that were utilized to combat helminths. There were 43 plants identified, divided into 24 families. seven plants were found to be the most culturally important plants in the management of helminths; these were Dioscorea deltoidea, Dioscorea bulbifera, Dioscorea alata, Gloriosa superba, Curcuma longa, Dioscorea pentaphylla, and Cyperus rotundus. The common phytochemical classes were phytosterols, tannins, alkaloids, saponins, essential oils, flavonoids, and terpenoids. Conclusions: Dioscorea deltoidea, Dioscorea bulbifera, Dioscorea alata, Gloriosa superba, Curcuma longa, Dioscorea pentaphylla, and Cyperus rotundus were shown to be the most culturally important plants for helminth control. These plants are mostly found in India and Nepal. There is need to investigate other tuberous plants to identify unique compounds that are active against helminths to develop more robust anthelminthic drugs and reduce anthelmintic resistance levels. Keywords: Anthelmintic, ethnobotanical, tubers, active compound, anthelmintic resistance, livestock